2013
DOI: 10.1186/1471-2229-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of a core collection of flax (Linum usitatissimum L.) suitable for association mapping studies and evidence of divergent selection between fiber and linseed types

Abstract: BackgroundFlax is valued for its fiber, seed oil and nutraceuticals. Recently, the fiber industry has invested in the development of products made from linseed stems, making it a dual purpose crop. Simultaneous targeting of genomic regions controlling stem fiber and seed quality traits could enable the development of dual purpose cultivars. However, the genetic diversity, population structure and linkage disequilibrium (LD) patterns necessary for association mapping (AM) have not yet been assessed in flax beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 78 publications
8
72
0
1
Order By: Relevance
“…These results suggest that Canadian flax cultivars have similar backgrounds, a relatively narrow genetic base, and low genetic diversity. This corroborates the results of Soto-Cerda et al (2013a) that show all 31 Canadian cultivars present in a germplasm collection of 407 core collection flax accessions cluster together on the basis of 414 neutral DNA markers. While the entire core collection has 2202 alleles, the Canadian cultivars only have 1081.…”
Section: The Genetic Base Of Canadian Flax Cultivarssupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggest that Canadian flax cultivars have similar backgrounds, a relatively narrow genetic base, and low genetic diversity. This corroborates the results of Soto-Cerda et al (2013a) that show all 31 Canadian cultivars present in a germplasm collection of 407 core collection flax accessions cluster together on the basis of 414 neutral DNA markers. While the entire core collection has 2202 alleles, the Canadian cultivars only have 1081.…”
Section: The Genetic Base Of Canadian Flax Cultivarssupporting
confidence: 89%
“…Molecular evaluation via 448 microsatellite markers has demonstrated that the core collection has abundant genetic diversity and a weak population structure, making it suitable for association mapping of agronomic and quality traits in flax (Soto-Cerda et al 2013b). Important agronomic traits such as seed yield, oil content and quality, fiber traits, and disease resistance have been phenotyped at multiple locations and years (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Several linear and mixed models have been proposed to correct the population structure and reduce the false positive factors (Pritchard et al 2000;Price et al 2006;Yu et al 2006). Association mapping in linseed have been carried out for various agronomic and seed quality traits (Soto-Cerda et al 2013 using SSR markers. Soto-Cerda et al (2013) identified 12 QTLs for six agronomic traits while 9 QTLs were identified for seed quality traits (Soto-Cerda et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Association mapping in linseed have been carried out for various agronomic and seed quality traits (Soto-Cerda et al 2013 using SSR markers. Soto-Cerda et al (2013) identified 12 QTLs for six agronomic traits while 9 QTLs were identified for seed quality traits (Soto-Cerda et al 2014). In the present investigation only 1 QTL was potentially identified for days to 50% flowering.…”
Section: Discussionmentioning
confidence: 99%
“…Later it was introduced into New World (The Americas) after vast spread throughout Asia and Europe (Soto-Cerda 2013). Indian subcontinent near the Mediterranean Sea is known to have high biological diversity of genus (Genesar and Morris, 2003;Fu, 2005;Kaur 2017).…”
Section: Plant Materials and Field Experimentsmentioning
confidence: 99%